Synthesis of green nano iron particles (GnIP) and their application in adsorptive removal of As(III) and As(V) from aqueous solution - Prasad, Kumar Suranjit; Gandhi, Pooja; Selvaraj, Kaliaperumal (Applied Surface Science, 2014)
{The present study reports a new approach to synthesise nano iron particles using leaf extract of Mint (Mentha spicata L.) plant. The synthesised GnIPs were subjected to detailed adsorption studies for removal of arsenite and arsenate from aqueous solution of defined concentration. Iron nanoparticles synthesised using leaf extract showed UV-vis absorption peaks at 360 and 430 nm. TEM result showed the formation of polydispersed nanoparticles of size ranging from 20 to 45 nm. Nanoparticles were found to have core-shell structure. The planer reflection of selected area electron diffraction (SAED) and XRD analysis suggested that iron particles were crystalline and belonged to fcc (face centred cubic) type. Energy-dispersive X-ray analysis (EDAX) shows that Fe was an integral component of synthesised nanoparticles. The content of Fe in nanoparticles was found to be 40%, in addition to other elements like C (16%), 0 (19%) and Cl (23%). FT-IR study suggested that functional groups like NH
Keywords: Adsorption; Arsenate; Arsenite; Iron nanoparticles; kinetics; M. spicata L.